Proper cleaning of keratin beetles reveals a cryptic species: Phoberus fumarius (Haaf, 1953) from southern Africa is reinstated as valid (Coleoptera: Trogidae) - Strümpher, Werner P.; Stals, Riaan (Zootaxa, 2021)
Among the southern African Trogidae, Trox fumarius Haaf, 1953 is presently considered a junior subjective synonym of Phoberus cyrtus (Haaf, 1953). The availability of more specimens than were seen by previous workers, coupled with thorough removal of cuticular dirt and accumulated debris, allowed in-depth morphological study of these nominal taxa and reassessment of their synonymy. Consistent differences in external morphology and in aedeagal structure are observed. Trox fumarius is removed from synonymy with Phoberus cyrtus, reinstated as a separate species, and transferred to the genus Phoberus MacLeay, 1819. Both species are diagnosed and redescribed. Photographs of their holotypes and of cleaned specimens illustrate them. The distributions of these two putatively sister species are discussed along with their probable habitat associations. The species are allopatric and have non-overlapping associations with biomes and habitats. Phoberus cyrtus is reported from Botswana for the first time. The importance of properly cleaning terricolous beetles covered with dirt and debris that obscure taxonomic features is emphasised and guidelines to achieve this are presented.